Exploring opportunities to incorporate systems thinking into secondary and tertiary chemistry education through practitioner perspectives. Issue 16 (2nd November 2021) - Delaney, Seamus; Ferguson, Joseph Paul; Schultz, Madeleine
ABSTRACT: Recently, the chemistry education community has focused considerable effort on incorporating systems thinking into chemistry education as a means to address global challenges such as sustainability. In this project, a series of exploratory workshops was held with secondary educators ( N = 12) and tertiary educators and researchers ( N = 16), introducing the participants to systems thinking in chemistry education (STICE). Following the workshops, small group semi-structured interviews were conducted to obtain deeper insight into how participants perceived systems thinking in relation to their teaching and research practice. Inductive analysis identified five major themes shared across both cohorts, relating to the perceived affordances and challenges of implementing systems thinking in chemistry education. The paper discusses these themes in relation to curriculum reform efforts, specifically with respect to pre-conditions needed for successful implementation in order to achieve the benefits of systems thinking in the classroom. We propose a possible pathway to realise these advantages.